Liver Transplantation With Older Donors: A Comparison With Younger Donors in a Context of Organ Shortage. Issue 11 (November 2016) - Barbier, Louise; Cesaretti, Manuela; Dondero, Federica; Cauchy, François; Khoy-Ear, Linda; Aoyagi, Takeshi; Weiss, Emmanuel; Roux, Olivier; Dokmak, Safi; Francoz, Claire; Paugam-Burtz, Catherine; Sepulveda, Ailton; et al.
Abstract : Background: Older liver grafts have been considered in the past decade due to organ shortage. The aim was to compare outcomes after liver transplantation with either younger or older donors. Methods: Patients transplanted in our center between 2004 and 2014 with younger donors (younger than 60 years; n = 253) were compared with older donors (older than 75 years; n = 157). Multiorgan transplantations, split grafts, or non–heart-beating donors were not included. Results: Donors in the older group were mostly women deceased from stroke, and only 3 patients had experienced cardiac arrest. Liver tests were significantly better in the older group than in the younger group. There was no difference regarding cold ischemia time, model for end-stage liver disease score, and steatosis. There was no significant difference regarding primary nonfunction and dysfunction, hepatic artery and biliary complications, and retransplantation rates. Graft survival was not different (65% and 64% in the older and younger groups, P = 0.692). Within the older group, hepatitis C infection, retransplantation, and emergency transplantation were associated with poor graft survival. Conclusions: Provided normal liver tests and the absence of cardiac arrest in donors, older liver grafts (>75 years) may be safely attributed to non–hepatitis C-infected recipients in the setting of a first and nonurgent transplantation. Abstract : This single center study evaluated outcomes of 157 livers obtained from donors over 75 years of age and compared them to a younger cohort. With appropriate selection these donors were associated with comparably good outcomes.